1989
DOI: 10.1159/000238685
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Childhood Bacterial Meningitis with Ceftriaxone Once Daily: Open, Prospective, Randomized, Comparative Study of Short-Course versus Standard-Length Therapy

Abstract: Fifty-two children were included in this study to evaluate and compare short- versus standard-length ceftriaxone therapy for bacterial meningitis. The duration of the short-course regimens was 4, 6 and 7 days for Neisseria meningitidis, Hemophilus influenzae and Streptococcus pneumoniae, respectively. The standard-length regimens were twice as long. On the basis of a computer-generated randomization list, 26 children were assigned either to the short- or to the standard-treatment regimen. Ceftriaxone was given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 17 publications
0
20
0
1
Order By: Relevance
“…Previous studies have shown similar CFR and recovery rates without sequelae at 72 h to those in our study. 5,13,14,22,23 All deaths reported in our study took place within 30 h of admission, and all occurred in patients who presented with impaired consciousness at admission. Furthermore, two-thirds of the patients who died had been diagnosed with another infection, either alone or associated with meningococcal meningitis.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Previous studies have shown similar CFR and recovery rates without sequelae at 72 h to those in our study. 5,13,14,22,23 All deaths reported in our study took place within 30 h of admission, and all occurred in patients who presented with impaired consciousness at admission. Furthermore, two-thirds of the patients who died had been diagnosed with another infection, either alone or associated with meningococcal meningitis.…”
Section: Discussionmentioning
confidence: 82%
“…Other studies testing short-course treatment (2-4 days) of ceftriaxone or chloramphenicol with longer follow-up periods than ours also failed to identify individuals with relapsed disease. [11][12][13][14][22][23][24] This scarcity of data could be explained by the fact that CSF is sterile 24-48 h after one injection of ceftriaxone or chloramphenicol. 11,[15][16][17][18]25 In both of our treatment groups, the CFR was lower than those reported from epidemiological surveillance or prospective studies undertaken during meningitis epidemics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No randomised trials exist in adults to support reduced duration. In children, there are a number of studies, including two smaller studies, [41][42] a meta-analysis 43 and a large multicentre, randomised, placebo-controlled trial, 44 that suggest that short-course therapy of 4-7 days is sufficient for acute bacterial meningitis. The latter study compared five vs. 10 days treatment with ceftriaxone for meningitis due Table IV.…”
Section: Bacteriamentioning
confidence: 99%
“…Although 7 days of therapy with ceftriaxone has been recommended for the treatment of meningococcal meningitis, several studies have demonstrated the efficacy of a single daily dose of ceftriaxone for 4 days [8], and several small studies have shown efficacy of 2-day courses of therapy [9,10]. Given the limitation of administration of multiple days of antimicrobial therapy of bacterial meningitis in the developing world, short-course therapy offers important advantages in ensuring that patients receive efficacious therapy.…”
Section: Editor's Commentsmentioning
confidence: 99%